Cognitive and Linguistic Aspects of Geographic Space New Perspectives on Geographic Information Research - Raubal, Martin; Mark, David M.; Frank, Andrew U.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
In 1990, sixty researchers gathered for two weeks at Castillo-Palacio Magalia in Las Navas del Marques, Spain, to discuss cognitive and linguistic aspects of geographic space. This meeting was the start of successful research on cognitive issues in geographic information science. It appeared worthwhile to assess the achievements and reconsider the research challenges twenty years later. What has changed in the age of computational ontologies and cyber-infrastructures? Consider that in 1990 the web was only about to emerge and the very first laptops had just appeared! The 2010 meeting brought together many of the original participants, but was also open to others. Scientists, engineers, and humanists working at the intersection of cognitive and geographic information science helped reassess the research needs and approaches. What are today$1 (Bs challenges? What can we achieve in the next 20 years? What are the lessons learned? This edited book evaluates the current state of the field through chapters by participants and documents an interdisciplinary research agenda for the future.s
Researching Cognitive and Linguistic Aspects of Geographic Space - Las Navas then and now -- Spatial Computing - How spatial structures replace computational effort -- The Cognitive Development of the Spatial Concepts NEXT, NEAR, AWAY and FAR -- From compasses and maps to mountains and territories: Experimental results on geographic cognitive categorization -- Prospects and Challenges of Landmarks in Navigation Services -- Landmarks and a hiking ontology to support wayfinding in a national park during different seasons -- Talking about Place Where It Matters -- Many to Many Mobile Maps -- Cognitive and linguistic ideas in geographic information semantics -- Spatial Relation Predicates In Topographic Feature Semantics -- The Egenhofer-Cohn Hypothesis$1 (Bor, Topological Relativity? -- Twenty Years of Topological Logic -- Reasoning on Class Relations: an Overview -- Creating perceptually salient animated displays of spatiotemporal coordination in events -- Exploring and Reasoning about Perceptual Spaces for Theatre, New Media Installations and the Performing Arts.s
Keywords: Geography; Geographical information systems; Geography; Geographical Information Systems/Cartography.; Electronic books